Problems of Heirless Property in Contemporary Russian Legislation - Anatolyi Borisovich Yelizarov (Сибирское юридическое обозрение)
The article highlights the issues of inheritance of escheat property. The problems associated with the mechanism to determine the property as escheat, as well as ways to transfer the property to the state. The author describes the essence of legislative measures which may be taken to tackle the challenges regarding escheat of property inheritance. In particular, it points to the need to identify bodies, which, on behalf of the state were not only entitled but also obliged to participate in the process of inheritance: the identification of escheat property, the receipt of a certificate of inheritance, the participation in court cases in this category, etc.